THE REVIEW OF THE TEXTS IN THE CONTEXT OF THE VALUES IN “TURKISH TEXT BOOK FOR SEVENTH-GRADE” PUBLISHED BY THE MINISTRY OF NATIONAL EDUCATION - Ecerkale, Nejla; Bayrak, Özcan (Ahmet KARA, 2018)
In the present study, the existence of values in texts of Turkish text book prepared by the Ministry of National Education for seventh grade students is analyzed. In the opening chapter of the study section contains definition, classification and functions of value, values education, place of value in syllabuses texts in the book, values studied and findings regarding these values. In the research, eighteen texts in the six themes in Turkish text book prepared by the Ministry of National Education for seventh grade students are examined. As a result of this examination, it is determined that which values are present in the texts and which ones are not. As a result of the review, the values determined in the abovementioned text book are modesty, determination, peace, success, scientificity, unity, bravery, diligence, friendship, sensitiveness, honesty, aesthetics, equity, self-sacrifice, geniality, tolerance, mercy, kindness, hospitality, respect, love, responsibility, cleanliness, patriotism. However, the justice, as a value, could not be determined in this book. The most mentioned value in the texts is aesthetics. After this, the order of other values is as follows: sensitiveness, patriotism, success, kindness, scientificity, diligence, friendship, unity, bravery, love, self-sacrifice, geniality, respect, responsibility, determination, honesty, modesty, peace, equity, mercy, cleanliness and tolerance.

Bu çalışmada Milli Eğitim Bakanlığının hazırladığı 7. sınıf Türkçe ders kitabında yer alan metinlerde belirlenen değerlerin varlığı incelenmiştir. Araştırmanın giriş  bölümünde değerin tanımı, snıflandırılması, işlevleri, değerler eğitimi, programda değerin yeri ve kitaptaki metinler, incelenen değerler, bu değerlere ait bulgular yer almıştır.Araştırmada Milli Eğitim Bakanlığının hazırladığı 7. sınıf Türkçe kitabındaki altı tema içerisinde bulunan on sekiz metin incelenmiştir. Bu inceleme neticesinde metinlerde yer alan değerler ve yer almayan değerler belirlenmiştir.İncelemenin sonucunda; Millî Eğitim Bakanlığının hazırladığı 7. Sınıf Türkçe Ders Kitabı’nda alçakgönüllülük, azim, barış, başarı, bilimsellik, birlik-beraberlik, cesaret, çalışkanlık, dostluk, duyarlık, dürüstlük, estetik, eşitlik, fedakarlık, güleryüz-tatlı dil, hoşgörü, merhamet, misafirperverlik, nezaket, saygı, sevgi, sorumluluk, temizlik, vatanseverlik değerleri tespit edilmiştir. Adalet değeri ise tespit edilememiştir. Metinlerde en çok işlenen değer estetiktir. Estetik değerini sırası ile   duyarlık, vatanseverlik, başarı, nezaket, bilimsellik, çalışkanlık, dostluk, birlik-beraberlik, cesaret, sevgi, fedakârlık, güleryüz-tatlı dil, saygı, sorumluluk, azim, dürüstlük, alçakgönüllülük, barış, eşitlik, merhamet, temizlik, hoşgörü değeri takip etmiştir.
TÜRKÇE 7. SINIF DERS KİTABINDAKİ METİNLERİN DEĞERLER BAĞLAMINDA İNCELENMESİ
Keywords: Studies on Education; Eğitim Üzerine Çalışmalar